2014
DOI: 10.1159/000362535
|View full text |Cite
|
Sign up to set email alerts
|

Advice on Lifestyle Changes (Diet, Red Wine and Physical Activity) Does Not Affect Internal Carotid and Middle Cerebral Artery Blood Flow Velocity in Patients with Carotid Arteriosclerosis in a Randomized Controlled Trial

Abstract: Background: A Mediterranean diet, with and without small daily amounts of red wine, and physical activity reduce the risk of cerebrovascular disease and improve cognition. An increase in cerebral blood flow may be the underlying mechanism. Under normal conditions, cerebral blood flow velocity changes in the internal carotid arteries and in large basal cerebral arteries correlate closely with cerebral blood flow changes, as the diameter of these vessels hardly changes and only the smaller vessels downstream cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Interestingly, for participants who only received lifestyle interventions in our study, the kinematic indices such as V max and V min as well as CVHP score at week 2 were a little lower than those at the baseline, and the dynamic indices such as Rv and CP were a little higher, which revealed that the cerebrovascular hemodynamic function was not much improved in the lifestyle intervention alone group. Tis outcome is consistent with some studies, which similarly found that the advice on lifestyle changes did not afect cerebral blood fow velocity in patients with carotid arteriosclerosis [32]. Nevertheless, some other studies have demonstrated that lifestyle interventions play a positive role in stroke prevention [33,34].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, for participants who only received lifestyle interventions in our study, the kinematic indices such as V max and V min as well as CVHP score at week 2 were a little lower than those at the baseline, and the dynamic indices such as Rv and CP were a little higher, which revealed that the cerebrovascular hemodynamic function was not much improved in the lifestyle intervention alone group. Tis outcome is consistent with some studies, which similarly found that the advice on lifestyle changes did not afect cerebral blood fow velocity in patients with carotid arteriosclerosis [32]. Nevertheless, some other studies have demonstrated that lifestyle interventions play a positive role in stroke prevention [33,34].…”
Section: Discussionsupporting
confidence: 89%
“…In patients with carotid atherosclerosis, the combination of a polyphenol-rich Mediterranean diet and moderate daily physical activity (30 min/day) with moderate red wine consumption (100 mL for women and 200 mL for men) for 20 weeks did not affect the middle cerebral and internal carotid blood flow velocity [ 27 ]. The absence of significant improvement may be due to the fact that 66% of the study population was on statin therapy [ 27 ]. However, in the same patient population, these lifestyle changes (healthy diet plus red wine, and exercise) for 20 weeks did improve the LDL/HDL ratio of the participants [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In young healthy individuals, low blood concentrations of ET following RW intake had an acute depressant effect on left ventricular (LV) performance, but an increase in some indices of right ventricular function [65], suggesting that low ET doses may impair LV function. A lifestyle modification intervention (including RW consumption) did not affect the blood flow velocity of the internal carotid or middle cerebral artery in patients with carotid atherosclerosis [76]. Most of the enrolled patients were receiving statin therapy, however, which could have hidden the beneficial effects on blood flow velocity and thus affected the study results.…”
Section: Cardiovascular Functionmentioning
confidence: 92%